Surgical outcome of radioguided parathyroidectomy in primary hyperparathyroidism - Nalbo, Dinesh; Dahiya, Divya; Sood, Ashwani; Bhadada, Sanjay Kumar; Behera, Arunanshu; Nahar, Uma (International Surgery Journal, 2021)
Background: Focused parathyroidectomy is the adequate treatment for primary hyperparathyroidism for localised disease. Adequacy of resection is confirmed by the availability of intraoperative parathormone assay (iOPTH). In the absence of availability of iOPTH assay, the radio guided surgery is an option. The aim of this study was to evaluate the feasibility of radioguided parathyroidectomy in tertiary care centre in India and to compare the overall success rate, operative time, hospital stay and postoperative outcome between focused open and radioguided parathyroidectomy. Methods: This was a prospective study which included 30 primary hyperparathyroidism patients with a single gland disease localised on Tc99m Sesta MIBI scan. Patients were randomized into two equal groups, and they underwent focused open or radioguided parathyroidectomy. Patients were followed up for three months. Results: All patients achieved biochemical cure as evident by the normalization of serum calcium and parathormone levels after surgery. The mean incision length, and operative time in this study was significantly better for radioguided parathyroidectomy (p=0.0001, <0.0001 respectively). There was no perioperative complications like recurrent laryngeal nerve injury, gland rupture, or bleeding in either group. However, there seems to be higher grade of pain experience by the patients who underwent open focused parathyroidectomy (p<0.0001). Conclusions: Radioguided parathyroidectomy has excellent cure rate for PHPT with an added advantage of short operative time & incision length and less post-operative pain. Radioguided parathyroidectomy seems to be a good alternative in the absence of availability of iOPTH assay and frozen section.